A Modeling Study of the Pore Size Evolution in Lithium-Oxygen Battery Electrodes. Issue 8 (3rd June 2015) - Li, Xianglin
Abstract : This study develops a statistics model that investigates the microstructural evolution of porous electrodes and couples the micro structural changes with a computational fluid dynamics model to simulate the discharge performance of an 800-μm-thick electrode at 1 A/m 2 . This study considers the fact that pores that are too small to hold reactants, smaller than a critical pore size, do not contribute to the discharge of the battery. It is found that when the pore size of the electrode increases, the discharge capacity of the electrode first increases due to the improved mass transfer and then decreases due to the decrease of the effective surface area. For instance, when the critical pore size is set as 10 nm, the discharge capacity gradually increases from 86.6 to 214.8 mAh/gcarbon when the mean pore size of the electrode increases from 10 to 50 nm, followed by a capacity decrease to 150.8 mAh/gcarbon when the mean pore size further increases to 100 nm. This study also finds that alternating the discharge current between 0 (open circuit condition) and the setting current rate can increase the discharge capacity of the lithium-oxygen battery because the oxygen concentration in the electrode increases during the open circuit condition.